Sources and prevention of graft infection during long‐term ex situ liver perfusion. Issue 4 (22nd June 2021) - Eshmuminov, Dilmurodjon; Mueller, Matteo; Brugger, Silvio D.; Bautista Borrego, Lucia; Becker, Dustin; Hefti, Max; Hagedorn, Catherine; Duskabilova, Muhayyo; Tibbitt, Mark W.; Dutkowski, Philipp; Rudolf von Rohr, Philipp; Schuler, Martin J.; et al.
Abstract: Introduction: The use of normothermic liver machine perfusion to repair injured grafts ex situ is an emerging topic of clinical importance. However, a major concern is the possibility of microbial contamination in the absence of a fully functional immune system. Here, we report a standardized approach to maintain sterility during normothermic liver machine perfusion of porcine livers for one week. Methods: Porcine livers (n = 42) were procured and perfused with blood at 34°C following aseptic technique and standard operating procedures. The antimicrobial prophylaxis was adapted and improved in a step‐wise manner taking into account the pathogens that were detected during the development phase. Piperacillin‐Tazobactam was applied as a single dose initially and modified to continuous application in the final protocol. In addition, the perfusion machine was improved to recapitulate partially the host's defense system. The final protocol was tested for infection prevention during one week of perfusion. Results: During the development phase, microbial contamination occurred in 27 out of 39 (69%) livers with a mean occurrence of growth on 4 ± 1.6 perfusion days. The recovered microorganisms suggested an exogenous source of microbial contamination. The antimicrobial agents (piperacillin/tazobactam) could be maintained above the targeted minimal inhibitory concentration (8‐16 mg/L) only with continuous application. In addition to continuous application of piperacillin/tazobactam, partial recapitulation of the host immune system ex situ accompanied by strict preventive measures for contact and air contamination maintained sterility during one week of perfusion. Conclusion: The work demonstrates feasibility of sterility maintenance for one week during ex situ normothermic liver perfusion.